PENGARUH INFLASI SUKU BUNGA JUMLAH UANG BEREDAR DAN PENDAPATAN NASIONAL TERHADAP NILAI TUKAR RUPIAH PER US DOLLAR - Haryadi, Haryadi (Jurnal Paradigma Ekonomika, 2014)
Abstract The aim of this research is to analyze the impact of inflation, interest rates, money supply and national income on Indonesian exchange rate. Time series data during the period of 2000-2012 has been employed in this research, meanwhile The Error Correction Model (ECM) has been used as a tool of analysis. The result of this research is in the long term variabel inflation and money supply has a significantly impact on exchange rate, in other hand variabel interest rate and national income has no a significantly impact. The coefficient of ECT at -2.5563 indicate that the proportion of the balance and the development of the exchange rate in the prior period has been adaptation in nowadays is -255.65. The implication of this research is that the government should make a policy to maintain exchange rate stability and the influence factors of it, such as inflation, interest rates, money supply and national income, especially in times of the excessive increasing on exchange rate. This condition is caused by the impact of adaptation exchange rate policies that not only concern on issues of macro stability, but also have a significant impact on the export and import incentives. The appreciation of exchange rate will be reduces the competitiveness of export goods, and increasing import penetration. Â  Keywords : determinant, exchange rate, error correction models